The impact of antipsoriatic treatment on serum pro-BDNF, BDNF levels, depression, anxiety scores, and quality of life - SEÇKİN GENÇOSMANOĞLU, DİLEK; AKKİPRİK, MUSTAFA; ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2021)
Depression is a comorbidity of psoriasis. Suppression of neurotrophins has been proposed to cause depression. Peripheral brain-derived neurotrophic factor (BDNF) and its precursor, pro-BDNF have been shown to be altered in depression. To compare serum pro-BDNF and BDNF levels, depression, anxiety, and quality of life (QoL) in psoriasis patients, diseased, and healthy controls, to assess impact of 12-week antipsoriatic treatment on abovementioned markers. At baseline, all groups completed Beck Depression Inventory (BDI), Spielberger State-Trait Anxiety Inventory-II (STAI-II) and DLQI; serum BDNF, proBDNF levels were measured. These were repeated after 3-months of treatment in psoriasis patients. Depression and anxiety were significantly higher, QoL was poorer in psoriasis. ProBDNF and proBDNF/BDNF ratios were not different among groups at baseline but significantly decreased after treatment in psoriasis. Depression and QoL improved significantly, BDNF and anxiety scores did not change. Altered pro-BDNF and proBDNF/BDNF ratios may have a role in depression pathogenesis in psoriasis. Antipsoriatic treatment causes improvement in depression, QoL, and reduction of proBDNF and proBDNF/BDNF ratios. Effective disease control may reverse dysregulated neurotrophin pathways and its consequences like depression.
Keywords: anxiety; BDNF; depression; proBDNF; psoriasis; quality of life